SOLAR THERMAL ENERGY: WATER HEATING INNOVATION FOR INDUSTRIAL PROCESSES - Carreira Junior, E. F.; Sacomano, J. B.; Mollo Neto, M. (Revista Brasileira de Engenharia de Biossistemas, 2014)
The increase of energy consumption worldwide has led to the search for alternative in energy sources, including solar, easy to use, which doesn´t require very sophisticated or complex equipment. Many industrial processes use water at temperatures up to 100 ° C. The use of solar energy in industry is still low if compared to the total energy consumption. The objective of this paper is to investigate possibilities of solar heating uses of water in industrial processes, for what it was search in international papers to identify these applications current stage all around the world. Exploratory research of secondary data from the Brazilian market systems, solar heating in the National Department of Solar Heating (DASOL), and the National Energy Efficiency Plan 2010-2030 (PNEF-2010) of the Ministry of Mines and Energy, sought to characterize the current state of this sector in Brazil. The study concludes that the solar water heating in Brazilian industries is possible and represents an alternative that can contribute to reducing cost and energy consumption by 30% to 40% of the heating process at low temperature, particularly in the food, beverage, textile and chemical sectors.